Integration and hedging efficiency between Brazilian and US ethanol markets - Capitani, Daniel Henrique Dario; Cruz Junior, José César; Tonin, Julyerme Matheus (Contextus - Revista Contemporânea de Economia e Gestão, 2018)
This study proposes to assess the ethanol market integration between U.S. and Brazil focusing on the investigation of the existence of an international ethanol price reference. We estimate a structural vector autoregressive model with error correction (SVEC) while considering not only ethanol sugar and corn prices in Brazil and in the U.S. but also international oil prices. Then we examine simultaneous hedging strategies by considering domestic and foreign futures contracts positions in the CME, NYMEX, and BM&FBOVESPA futures exchanges. Our results highlight a weak integration between U.S. and Brazil ethanol markets, as well as low levels of hedge effectiveness in using foreign ethanol futures contracts, which suggests the absence of a price reference in the global market.